Case Report: The Coronal Magnetic Resonance Imaging of Three-Dimensional Fast-Field Echo With Water-Selective Excitation Can Identify the Wrapping of Spinal Nerve Fibers Into Subdural Tumors Prior to Operation - Tang, Tao; Yuan, Jinghong; Yin, Jianhua; Zhu, Junchao; Jia, Jingyu; Cheng, Xigao (Frontiers in Neurology, 2022)
Purpose In the present study, the authors intend to identify the spatial relationship between subdural tumors and spinal nerve fibers of cauda equina prior to operation using the coronal MRI of three-dimensional fast-field echo with water-selective excitation (CMRI). Methods In total, 30 case series with surgically and pathologically verified subdural tumors were enrolled in the present study. The spatial relationship between subdural tumors and spinal nerve fibers of the cauda equina was assessed via conventional MRI and CMRI by three experts prior to operation. The spatial relationship between subdural tumors and spinal nerve fibers of the cauda equina was classified using CMRI. The accuracy of imaging observation was determined via intraoperative observation. Results Though conventional MRI and gadolinium (Gd)-enhanced MRI (Gd MRI) cannot identify the spatial relationship between subdural tumors and spinal nerve fibers of cauda equina in all cases, CMRI can identify it prior to operation and divide the spatial relationship of spinal nerve fibers of cauda equina with subdural tumors into three types. CMRI shows higher sensitivity (97.44%) and specificity (90.47%) in identifying the spatial relationship of spinal nerve fibers of cauda equina with subdural tumors. Additionally, CMRI also showed a substantial agreement with a kappa value of 0.78. Conclusion Herein, the authors first describe a potential novel application that CMRI can successfully identify the spatial relationship between subdural tumors and spinal nerve fibers of cauda equina prior to operation, which play an essential role in making a prudent surgical plan and preventing postoperative nerve damage. Summary Intraoperative observation confirms spinal nerve fibers of cauda equina are often wrapped into subdural tumors of the thoracolumbar and lumbar region, which can result in a high rate of sensory and motor dysfunction after the operation due to the unconscious about the wrapping of nerves into subdural tumors prior to operation. To date, there is not an effective strategy to identify the wrapping before operation.